Necrotizing Enterocolitis: Clinical Features, Histopathological Characteristics, and Genetic Associations - Maheshwari, Akhil; Traub, Terri M.; Garg, Parvesh M.; Ethawi, Yahya; Buonocore, Giuseppe (Current Pediatric Reviews, 2022)
Necrotizing enterocolitis (NEC) is an inflammatory bowel necrosis seen in premature infants. Although the etiopathogenesis of NEC is unclear, genetic factors may alter a patient's susceptibility, clinical course, and outcomes. This review draws from existing studies focused on individual genes and others based on microarray-based high-throughput discovery techniques. We have included evidence from our own studies and from an extensive literature search in the databases PubMed, EMBASE, and Scopus. To avoid bias in the identification of studies, keywords were short-listed a priori from anecdotal experience and PubMed’s Medical Subject Heading (MeSH) thesaurus.
Keywords: histopathology